Service management in IT-enabled service supply chains - Wang, Yan, (SAGE Knowledge. Cases., 2017)
Services and information technology (IT) are dominating the current global economy. Due to the increasing involvement of IT in service operations, a new type of service supply chain (SSC) has emerged, namely the IT-enabled SSC. The present case is intended to reveal the insights of service management in such a new supply chain. Through the example of TeleSP, a northern European telecommunications and IT service provider with a complex supply chain, readers are invited to discover the unique characteristics of the IT-enabled SSC, and to view the challenges in running it.